The FASTER Principles for Successful Carbon Pricing : An Approach Based on Initial Experience - OECD; World Bank Group (World Bank, Washington, DC, 2015)
The case for climate action has never been stronger. Current weather extremes, including storms, floods and drought, affect millions of people across the world. Climate change is putting water security at risk; threatening agricultural and other supply chains as well as many coastal cities. The likelihood of severe pervasive and irreversible impacts will grow without action to limit and reverse the growth of GHG emissions globally. Last year’s Intergovernmental Panel on Climate Change (IPCC) report makes clear the overwhelming need to take action now on climate change and that the costs of inaction will only rise. The challenge is to decarbonize our economies by 2100 with action in the next decades being critical. The choices made by government, the private sector, and civil society as part of the transition to a decarbonized economy will determine the extent of future climate impacts but also provide an opportunity to unlock investment and build an innovative, dynamic low-carbon economy.